Wpływ podłoża na wzrost jednoletnich i dwuletnich sadzonek jodły pospolitej i buka zwyczajnego produkowanych w kontenerach styropianowych - Banach, Jacek; Skrzyszewska, Kinga; Świeboda, Łukasz (Leśne Prace Badawcze, 2013)
The effectiveness of different peat-based substrates was compared for the propagation of two mountain tree species (silver fir and European beech). The experiment was set up in spring of 2006, and seedlings were grown in polystyrene multipots for 2 years. Four types of substrate were applied: (1) newly prepared 1:1 peat-sawdust mixture ; (2) a peat-sawdust mixture which had already been used for five production periods; (3) a peat substrate produced in the ‘Nędza’ container nursery (Rudy Raciborskie Forest District), consisting of peat and perlite; (4) a peat substrate, as described for (3), with added mycorrhizal fungus Hebeloma crustuliniforme. After sowing, polystyrene multi-pots were placed in a transparent tent. During the autumns of 2006 and 2007, for both species and each substrate type, 25 seedlings were randomly selected for measurement of their above-ground height, root length, root collar diameter, above- and below-ground fresh weight. Growth of one-year old and two-year-old seedlings of both species differed depending on their substrate. The application of a mycorrhizal inoculum positively affected seedling establishment, since the best height growth and largest seedlings of both species were grown on substrate (4). The growth of one-year-old fir seedlings in the ‘old’ peat and sawdust mixture (2) was similar to those seedlings on the turf substrate (3). Root:shoot allocation differed among the substrates. In fir root:shoot allocation was approximately equivalent at 1:0.9, whereas for beech it was 1:2 in one-year-old seedlings and 1:1.5 in two-year-old seedlings.